1991
DOI: 10.1002/jemt.1060180303
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the physical structure of biological materials at biosensor interfaces by techniques of increasing magnification from microscopic to molecular scale

Abstract: Chemical selectivity of biosensors is derived from biological materials interfaced to the surface of transducing devices. Molecular recognition events lead to macroscopic function suitable for analytical measurements. The structure-function relationships of biochemical species at interfaces must be established to characterize and optimize biosensor operation. The techniques of ellipsometry, fluorescence microscopy, electron microscopy, and scanning tunneling microscopy are used to investigate the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Incorporation of Ox lpp-scFv to the matrix made the film more stable. This agrees with earlier results on proteins having a stabilizing effect on monolayers. , …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Incorporation of Ox lpp-scFv to the matrix made the film more stable. This agrees with earlier results on proteins having a stabilizing effect on monolayers. , …”
Section: Resultssupporting
confidence: 94%
“…The antibodies have a random distribution at the air−water interface 2-4 and site-directed immobilization could not be obtained by adsorption. Fab‘ fragments have been used in order to improve orientation and surface density. , Fab‘ fragments covalently bound to phospholipids have been embedded into a monolayer by fusion from vesicles …”
Section: Introductionmentioning
confidence: 99%
“…177,179,180 Oriented surface lms have also been proposed and utilized as biosensors. [182][183][184][185][186] Langmuir-Blodgett (LB) m onolayer and multilayer lms have been used in pyroelectric infrared detectors, [187][188][189] and have potential for use in a wide variety o f optoelectron ic ap plications. 178,187,188,190 The rst step toward develo pin g and in tegratin g these technologies into complex systems is the generation of highly oriented lms of micrometer thickness.…”
Section: Oriented Th In Film S For No Nlinear Optical Devicesmentioning
confidence: 99%
“…Antibodies can, however, be oriented on the surface by binding of the Fc region of the antibody to a layer of protein A or protein G (Turková, 1999). Fab -fragments can be covalently attached onto supported lipid layers and biotinylated antibodies can be coupled onto a surface coated by (strept)avidin (Morgan and Taylor, 1992;Vikholm and Albers, 1998;Fischer et al, 1993;Schönhoff et al, 1992;Krull et al, 1991;Heyn et al, 1990). In previous papers, we have shown that human IgG antibody Fab -fragments can be directly coupled onto gold and, moreover, that the space in between the fragments can be filled with non-ionic, hydrophilic disulphide bearing polymers that suppress non-specific binding (Vikholm and Sadowski, 2003;Vikholm-Lundin, 2005;.…”
Section: Introductionmentioning
confidence: 99%